Incidence of Axillary Adenopathy in Breast Imaging After COVID-19 Vaccination - Robinson, Kristin A. (JAMA Oncol, 2021)
This case series examines the incidence, timing, and characteristics of mammographic axillary adenopathy following COVID-19 vaccination.